Hepatic Resection Is Associated With Improved Long-Term Survival Compared to Radio-Frequency Ablation in Patients With Multifocal Hepatocellular Carcinoma - Yue, Yang-yang; Zhou, Wei-li (Frontiers in Oncology, 2020)
Background: The prognosis of patients with hepatocellular carcinoma (HCC) is of major public health interest. However, studies comparing hepatic resection (HR) and radio-frequency ablation (RFA) applied to multifocal HCC are limited. This study aimed to compare the efficacies of HR and RFA in patients with multifocal HCC. Methods: We retrospectively analyzed a cohort from the Surveillance, Epidemiology and End Results database between 2004 and 2015. Disease-specific survival and overall survival rates were assessed before and after propensity score matching (PSM). Results: In total, 2201 patients with multifocal HCC treated with HR (n=1095) or RFA (n=1106) were included; 1096 patients were identified after nearest-neighbor PSM at a ratio of 1:1 (HR: n=548; RFA: n=548). In the multivariate Cox regression model, HR was associated with significantly improved disease-specific survival (before PSM: hazard ratio 0.67, 95% confidence interval [CI] 0.57-0.79, p<0.001; after PSM: hazard ratio 0.69, 95% CI 0.58-0.82, p<0.001) and overall survival (before PSM: hazard ratio 0.67, 95% CI 0.58-0.78, p<0.001; after PSM: hazard ratio 0.69, 95% CI 0.59-0.80, p<0.001) compared to RFA in patients with multifocal HCC. In the survival curve analysis, the disease-specific survival of the HR group was similar to that of the RFA group before PSM (p=0.936, log-rank test) but was significantly longer after PSM (p<0.001) in all patients. Multivariate analyses revealed that differentiation grade, alpha-fetoprotein, tumor size and tumor extension were independent predictors of poor prognosis in patients with multifocal HCC. Conclusions: The long-term survival rate of HR is better than that of RFA in patients with multifocal HCC. HR may serve as a first-line treatment for patients with multifocal HCC. The presence of large tumors and vascular invasion are not contraindications for HR.